Determination of aromatic amines in environmental water samples using solid-phase extraction modified with sodium dodecyl sulphate and micellar liquid chromatography. Issue 5 (8th April 2016) - Hadjmohammadi, Mohammad Reza; Ebrahimi, Samira; S. J. Nazari, S. Saman
ABSTRACT: Extraction and determination of seven aromatic amines in environmental water samples were performed with solid-phase extraction (SPE) and micellar liquid chromatography (MLC) using experimental design. Extraction of aromatic amines was carried out with a C18 cartridge modified with sodium dodecyl sulphate (SDS). The washing solution and elution solvent for extraction of aromatic amines were aqueous solution containing 5% (v/v) acetonitrile and 5% (v/v) acetone and 3 mL methanol, respectively. The chemometrics approach was applied for the separation optimisation of these compounds using MLC. Different mobile phase compositions were used for modelling based on retention times to obtain the best separation using central composite design. The optimum mobile phase composition for separation and determination of analytes in water samples was 69 mM SDS, 9% v/v 1-propanol and pH = 6.4. Recoveries were between 84.8–93.5% with relative standard deviation (RSD) less than 5.8% ( n = 5). Limits of detection and linear range were 1–4.5 and 3.1–125.0 µg/L, respectively. The proposed method was applied to determine the aromatic amines in real samples (river and well waters). Amount of 4-nitroaniline and 3-nitroaniline in river water sample were 2.15 and 1.91 µg/L, respectively.